Study of Attitude Toward Homosexuality Among the Health Professionals - Vishal K. Patel; Vaibhav M. Joshi; Falguni B. Patel; Anand Barot; Vivek Sharma; Ronak Prajapati (Journal of Psychosexual Health)
Background: Despite the level of awareness of homosexuality is in the increasing trend, health professionals lack a positive attitude toward homosexuality. Aim: The purpose of this study was to determine the level of attitudes toward homosexuality among health professionals. Subject and Methods: This was a cross-sectional study conducted among 600 health professionals. The attitude toward homosexuality questionnaire was used to assess the attitude of health professionals toward homosexuality. A descriptive analysis, Mann–Whitney U test, and Kruskal Wallis test were used to analyze the data. Observations: The mean score for attitude toward homosexuality questionnaire was 73.04 + 23.39 among the participants. The males had lesser degree of positive attitude compared to higher degree of positive attitude of females toward homosexuality. Participants from rural areas had neutral attitudes, and participants from the urban areas had positive attitudes toward homosexuality. Participants living in nuclear families had positive attitudes toward homosexuality, and participants living in joint families had negative attitudes toward homosexuality. Participants with heterosexual orientation had negative attitudes toward homosexuality. Conclusion: Overall, health professionals had a lesser degree of positive attitude toward homosexuality; they require sensitization to upgrade their positive attitude toward homosexuality for better doctor–patient relationship.